On Large-Lifting and Large-Supplemented Modules - Abduljaleel, Amira A.; Yaseen, Sahira M. (Iraqi Journal of Science, 2022)
In this paper, we introduce the concepts of Large-lifting and Large-supplemented modules as a generalization of lifting and supplemented modules. We also give some results and properties of this new kind of modules.